Knowledge ecology for conceptual growth: teachers as active agents in developing a pluriliteracies approach to teaching for learning (PTL). Issue 3 (3rd April 2018) - Coyle, Do; Halbach, Ana; Meyer, Oliver; Schuck, Kevin
ABSTRACT: This article explores how a group of educators and researchers enacted an inclusive process of conceptual growth involving teachers and teacher educators as active agents, knowledge builders and meaning-makers in the development of a Pluriliteracies approach to Teaching for Learning (PTL). The evolution of a working model based on five emergent principles, foregrounded the need for stakeholders across different languages, cultures and disciplines, to work together from the start so that learning spaces were created where teacher development went alongside researcher development, and theorizing was not only inclusive of praxis but validated by it. A growth cycle emerged using theories of practice as the medium for critique, disagreement and consensus which this article seeks to interpret through an ecological lens. The development of the theoretical constructs, therefore, involves shared ownership and is embedded in the development of pedagogic practices. This approach does not end with a theoretical model but continues growing a principled practice model which prioritizes teacher agency for further critique and development.